Sudan : Selected Issues Paper. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2012)
This selected issues paper on Sudan was prepared by a staff team of the International Monetary Fund as background documentation for the periodic consultation with the member country. It is based on the information available at the time it was completed on September 7, 2012. The views expressed in this document are those of the staff team and do not necessarily reflect the views of the government of Sudan or the Executive Board of the IMF.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet